2004
DOI: 10.1093/geront/44.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Clinical Site Factors Associated With Rescreening Behavior Among Older Multiethnic, Low-Income Women

Abstract: Individual and health-care-delivery-system factors play important roles in the obtaining of regular mammograms by low-income women. These findings highlight the importance of both factors in improving rescreening rates among older women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
3
6
1
Order By: Relevance
“…Results of the multivariate Logistic regression for initial screening agreed with findings from other studies (Canadian Partnership Against Cancer, 2013, Zapka et al, 1989, Lerman et al, 1990, Katz and Hofer, 1994, Maxwell et al, 2001, McDonald and Sherman, 2010, Tang et al, 2000, Song and Fletcher, 1998, Sabogal et al, 2000, Barr et al, 2001, Rauscher et al, 2005, Bobo et al, 2004, Rosenberg et al, 2005, Calvocoressi et al, 2005, Fox et al, 2004). Results indicated certain demographic, geographic, and socioeconomic factors were significant determinants of both initial participation and retention but not always in the same direction.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Results of the multivariate Logistic regression for initial screening agreed with findings from other studies (Canadian Partnership Against Cancer, 2013, Zapka et al, 1989, Lerman et al, 1990, Katz and Hofer, 1994, Maxwell et al, 2001, McDonald and Sherman, 2010, Tang et al, 2000, Song and Fletcher, 1998, Sabogal et al, 2000, Barr et al, 2001, Rauscher et al, 2005, Bobo et al, 2004, Rosenberg et al, 2005, Calvocoressi et al, 2005, Fox et al, 2004). Results indicated certain demographic, geographic, and socioeconomic factors were significant determinants of both initial participation and retention but not always in the same direction.…”
Section: Discussionsupporting
confidence: 84%
“…Conditional on initial screening, retention rates have been found to be relatively high for subsequent screening, in contrast to initial screening rates, and this is reflected in the higher screening targets for subsequent rescreening (Canadian Partnership Against Cancer, 2015, Canadian Partnership Against Cancer, 2013). Among those studies examining rescreening (Song and Fletcher, 1998, Sabogal et al, 2000, Barr et al, 2001, Rauscher et al, 2005, Bobo et al, 2004, Rosenberg et al, 2005, Calvocoressi et al, 2005, Fox et al, 2004), some have identified demographic (Song and Fletcher, 1998, Sabogal et al, 2000, Rauscher et al, 2005, Rosenberg et al, 2005, Fox et al, 2004), socioeconomic (Song and Fletcher, 1998, Sabogal et al, 2000), psychological factors (Rauscher et al, 2005, Fox et al, 2004), medical history (Bobo et al, 2004), and cost (Bobo et al, 2004) as correlated with rescreening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also explore how the gender discrepancy varies by age, education, and income level, given the increased prevalence and severity of UI with aging, 11 and the impact of socioeconomic factors on primary care access and utilization. [12][13][14] …”
mentioning
confidence: 99%
“…Research on predictors of breast and gynecological cancer screening practices has focused mainly on sociodemographic/environmental factors (Hall, Uhler, Coughlin, & Miller, 2002;Harrison et al, 2003;Selvin & Brett, 2003) and women's knowledge and beliefs about screening (Crump, Mayberry, Taylor, Barefield, & Thomas, 2000;Fox et al, 2004;Rawl, Champion, Menon, & Foster, 2000). There is less research on the influence of psychologi-248 C. R. Barron et al cal variables, especially those representing personality characteristics (Siegler & Costa, 1994).…”
mentioning
confidence: 99%